Rediseño del manual de operación del bombero aeronáutico en base a la seguridad y los procesos de prevención de incendios en el Aeropuerto Internacional Cotopaxi - Falcony Hidalgo, Rolando Eugenio (2013)
The outdated and inefficiency of the Aeronautical Firefighter's Operation Manual have led to its redesign based on safety and fire prevention processes at the Cotopaxi International Airport. Among the most relevant contents of this thesis are: Operation of the Aeronautical Firefighter, the emergency plan and the fire prevention processes. The purpose of this research is to carry out a global redesign of the Aeronautical Firefighter's operating manual, complementing, updating and purifying the information that structures the total platform of the writing; of transcendence in the firefighter's operation. For this it is clear to perceive the feasibility of this project, which uses field research and bibliographic documentary research.